Futuristic Trends of ITEP(Integrated Teacher Education Program) in India under the Light of Nep-2020, A Boon or Bane: Exploring the Strategies, Challenges, and Trends of Integrated Teacher Education Program in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An educator is considered as the most innovative and one of a kind individual as in light of thefact that an instructor has the capacity to impact and rouse understudies through his keenness, beliefs,experience, shrewdness and dynamic character and for this reasons instructors are viewed as a genuinedraftsman of a country. After autonomy Administration of India had offered exceptional considerationtowards training area and set up different councils and commissions, but still India lingers behinddifferent nations in regard to educator schooling. To defeat this NCTE, under the Service of Training hasas of late presented the Public Schooling Strategy 2020 where a ton of new guidelines are reported forfruitful execution of Coordinated Instructor Schooling Project (ITEP). ITEP is a particularly planned fouryears incorporated program which includes a comprehensive four year certification offering B.A. B.Ed.B. Sc. B. Ed. furthermore, B.Com. ITEP will be useful for those understudies who need to join showingcalling in future. ITEP will be presented by the multidisciplinary establishments and it will be the baseessential capability to turn into a teacher. Anyway fruitful execution of ITEP is difficult for theorganizations and establishments should plan techniques for effective execution of ITEP in theirparticular foundations. This paper attempts to concentrate about the procedures, challenges and modernpatterns of Coordinated Educator Schooling Project in regard to NEP 2020.